Species diversity of non-tuberculous mycobacteria isolated from patients in the “pre-Covid” period and during the COVID-19 pandemic - Vasilyeva I.A.; Panova A.E.; Gracheva A.N.; Bayrakova A.L.; Kazyulina A.A.; Eliseev P.I.; Samoylova A.G. (Клиническая микробиология и антимикробная химиотерапия, 2024)
Objective.